Depression Among Cervical Cancer Patients: A Cross-Sectional Analysis of Clinical and Sociodemographic Factors - sharond, zhaqirra; Nefertiti , Eva Pravitasari; Nandaka, I Ketut Tirka (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2025)
Cervical carcinoma is a type of cancer that predominantly affects women and significantly impacts their quality of life, particularly psychological well-being. Depression is a common psychological complication experienced by cervical carcinoma patients. This study aims to analyze the characteristics of cervical carcinoma patients experiencing depression at RSPAL dr. Ramelan Surabaya in 2024. The research used a descriptive design with a retrospective approach, with data obtained from patient medical records and the Beck Depression Inventory (BDI) questionnaire. The analysis classified patients' depression levels into normal, mild mood disturbance, borderline depression, low depression, moderate depression, and extreme depression, while evaluating risk factors such as age, employment, and marital status. The results showed that the majority of patients were in the extreme depression category, with a percentage of 35.2%. Age-related risk factors revealed that 74.1% of patients were in the adult age group (19–59 years). Regarding employment, most patients were housewives or unemployed (68.5%). Furthermore, the majority of patients were married or previously married (85.2%). In conclusion, cervical carcinoma patients tend to experience extreme depression, particularly those in the adult age group, women who are unemployed, and those who are married. These findings are expected to serve as a reference for developing psychological intervention programs to improve the quality of life of cervical carcinoma patients